Test of Rotor Gap and Varian of Knife Edge Shape on Mechanical Coffee Pulper Equipment Singular Cylinder - Adella Ginting; Achwil Putra Munir; Nazif Ichwan (Jurnal Rekayasa Pangan dan Pertanian, 2015)
There were still found crushed coffee beans and unpeeled coffee in pulping of coffee. Quality of coffee was affected by rotor gap and blade variation. This research was held to test the rotor gap and blade variation on parameters measured, i.e effective capacity of the equipment, unpeeled beans percentage, crushed beans percentage, percentage beans in wet skin output and percentage wet skin in beans output. This research used factorial completely randomized design with two factors i.e rotor gap (0.8, 1.0, 1.2, 1.4 cm) and variant of blade (linear, curve, triangle and half of circle).The result showed that the rotor gap had significantly affected all parameters. Variant of blade had significantly affected all parameters except percentage beans in wet skin output. The interaction of the two factors had significantly affected all parameters except percentage beans in wet skin output and percentage wet skin in beans output. The best result was the combination of 1.0 cm gap with half of circle blade which resulted effective capacity of 170.79 kg/hour, unpeeled beans percentage of 8.33%, crushed beans percentage of 2.83%, percentage beans in wet skin output of 9.83% and percentage wet skin in beans output of 7.08%. Key words: coffee, pulping, rotor gap, blade